Why Stop Self-Injuring? Development of the Reasons to Stop Self-Injury Questionnaire. (January 2014) - Turner, Brianna J.; Chapman, Alexander L.; Gratz, Kim L.
We developed a measure of reasons to refrain from nonsuicidal self-injury (NSSI), the Reasons to Stop Self-Injury Questionnaire (RSSIQ), and examined how such reasons are associated with vulnerability versus resiliency for NSSI. Following qualitative item generation, we explored the factor structure, reliability, and convergent validity of the RSSIQ in 218 self-injuring undergraduates. In Study 2, we confirmed the hierarchical factor structure in 146 self-injuring individuals. In Study 3, we examined the incremental predictive validity of the RSSIQ. These studies resulted in a 40-item inventory with nine subscales and two higher-order factors. Resiliency-related reasons to stop NSSI were associated with greater hopefulness, social support, and adaptive coping, and prospectively protected against NSSI 3 months later, while vulnerability-related reasons were associated with greater psychopathology and dysfunctional coping, and predicted more chronic and severe NSSI. These studies, and the RSSIQ, can enhance the assessment and treatment of NSSI by clarifying motivations to stop NSSI.